Effects of lubricating oil on the performance of a semi-hermetic twin screw refrigeration compressor. (5th February 2017) - Wu, Xiaokun; Xing, Ziwen; He, Zhilong; Wang, Xiaolin; Chen, Wenqing
Highlights: Performance of an oil-injected twin-screw refrigeration compressor was studied. A methodical model and experimental set-up were developed for this purpose. The standard oil injection method lowered the compressor performance. A modified oil injection network was proposed and studied theoretically. The modified oil injection network improved the compressor performance. Abstract: Lubricating oil is often employed in a twin-screw refrigeration compressor for lubricating bearings, sealing leakage paths, cooling refrigerant gas and regulating capacity. In this paper, the effect of lubricating oil on the performance of a semi-hermetic twin-screw refrigeration compressor is investigated. A mathematical model is established and a comprehensive experimental investigation is performed for this purpose. The model is validated using experimental data and then used to investigate the effect on compressor performance of lubricating oil supplied to the suction and discharge end bearings, and returned to the suction pipe. The results show that the compressor performance is reduced as the compensation oil injection flow rate increases in the suction pipe. However, as the compensation oil injection position moves from the suction pipe to a proper compression chamber position, the compressor efficiencies increase as the oil flow rate increases. The results also show that the compressor performance decreases as the oil flow rate increases at the suction end bearing. But the effect on the compressor performance of the lubricating oil supplied to the discharge end bearing depends on the oil temperature. Low temperature oil supplied to the discharge end bearing increases the compressor performance, while high temperature oil lowers the compressor performance. These analyses provide useful information for optimizing lubricating oil distribution to maximize energy efficiency in semi-hermetic twin screw refrigeration compressors.